Faktory virulence a rezistence Pseudomonas aeruginosa - Maršík, Dominik (Chemické listy, 2021)
One of the most feared global threats to public health today is spread and development of highly resistant bacteria, including the opportunistic pathogen Pseudomonas aeruginosa. The treatment of already severe pseudomonas infections is significantly complicated by the bacterial resistance to virtually all antimicrobial drugs available on the market, including aminoglycosides, fluoroquinolones, and β-lactams, making it very difficult to eradicate compared to other pathogens. The spread of such bacterial clones is a serious risk to public health. This review aims to summarize the basic information about Pseudomonas aeruginosa with a focus on virulence factors and the mechanisms of resistance acquisition that bacteria use in pathogenesis.
Keywords: antibiotická rezistence; virulence; Humans; Drug Resistance, Microbial; Virulence; Pseudomonas aeruginosa; Pseudomonas Infections; pseudomonádové infekce; lidé